The Pleistocene lion Panthera spelaea (Goldfuss, 1810) from Poland – A review. (20th December 2021) - Marciszak, Adrian; Lipecki, Grzegorz; Pawłowska, Kamilla; Jakubowski, Gwidon; Ratajczak-Skrzatek, Urszula; Zarzecka-Szubińska, Katarzyna; Nadachowski, Adam
Abstract: Panthera spelaea was recorded in Poland from 18 open-air and 42 cave sites dated in the range 750–28 ka. Most of these records are located in southern Poland (Silesia) and neighbouring areas. Among them, the find of Panthera spelaea in Kozi Grzbiet mentioned here for the first time is one of the oldest European records of the species. Most of the obtained AMS dates are concentrated on the second half of MIS 3 and showed that the Pleistocene lion disappeared more or less synchronously across Poland. The findings of its remains from open-air sites are mostly accidental discoveries during field works, while those in caves are mostly connected with archaeological research and the exploitation of cave sediments for producing fertilizers. Aside of a few juvenile bones and milk teeth, the remains of adult individuals, mostly males, predominate in the studied sample. Their behavior to hunting cave bear during the times, when the other, more typical food sources were scarce, tendention to hunt very big preys and went into the conflicts with other carnivores than females do, resulted in higher injuries and mortalities. Within the species, three chronosubspecies were recognized, with P . s . fossilis recorded from 7 sites, dated between 750 and 240 ka and P . s . intermedia only partially recognized in Wierzchowska Górna Cave. The most numerous are the remains of P . s . spelaea which were found in 48 localities dated between 150 and 28 ka. With the exception of four caves, the Polish finds of P . spelaea are generally less abundant at sites where they occur. Older P . s . fossilis, dated on MIS 19–12, was a large form with robust stature and broad cheek teeth. Younger P . s . fossilis dated on MIS 11–9 was represented by a large and massive specimens, but with more advanced morphological dental features. Polish individuals of P . s . spelaea were slightly smaller and less massive than P . s . fossilis, with narrower cheek teeth. Since MIS 3, a dwarf and gracile specimens appeared, which is correlated with the genetic turnover ca. 48–45 ka. The Pleistocene lion was one of the earliest disappeared large carnivores predated only by a cave hyena. There are no direct evidences of P . spelaea encounters with humans. The extinction of P . spelaea is broadly correlated with the general collapse of the "mammoth steppe" ecosystem and was resulted of multiple reasons like climatic changes, re-building of herbivore guilds, competition and human pressure. Wolf and, to a lesser extent, bears were the main competitors for the Pleistocene lion in Poland.